Comparison of Surgical versus Conservative Approach in Management of Pancreatic Fistula Following Pancreaticoduodenectomy - Muhammad Amin, Najam ud Din, Hafeezullah, Irshad Ahmed, Habibullah, Ishtiaque Ali Langah, Jamshed Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To compare surgical versus conservative approach in managing pancreatic fistula following pancreaticoduodenectomy in terms of rate of fistula closure and mortality. Study Design: Prospective Comparative Study